Aggressive embryonal rhabdomyosarcoma in a 3-month-old boy: A clinical and molecular analysis. (17th November 2018) - Renzi, Samuele; Langenberg-Ververgaert, Karin; Fuligni, Fabio; Ryan, Anne Louise; Davidson, Scott; Anderson, Nathaniel; Hayes, Reid; Hopyan, Sevan; Gerstle, Justin T.; Shago, Mary; Chami, Rose; Malkin, David; et al.
Abstract: Rhabdomyosarcoma (RMS) represents the most common soft tissue sarcoma in the pediatric age group. While RMS has been traditionally classified on the basis of its histological appearance (with embryonal and alveolar being most common), it is now clear that the PAX-FOXO1 fusion product drives prognosis. We report here a case of pelvic embryonal RMS in a 3-month-old male who was subsequently found to have developed brain metastases during the course of chemotherapy. Cytogenetic analysis of the brain metastases at the time of autopsy as well as next-generation sequencing analysis revealed a reciprocal translocation involving the SH3 domain containing ring finger 3 gene (SH3RF3, on chromosome 2q13) and the Lipase C gene (LIPC, on chromosome 15q21.3). Due to the poor quality of the pretreatment and postresection samples, cytogenetics and NGS analysis looking for the presence of this balanced translocation in these specimens could not be performed. To the authors' knowledge, this translocation has never been described in RMS. Further studies are needed to determine the biological and clinical implications of this novel translocation.